Rhapsodic Inquiry and the Methodological Imaginal - Gary Levy (Reconceptualizing Educational Research Methodology, 2012)
This paper reflects on, and examines some issues sidelined during the writing of a doctoral dissertation that was completed at the end of 2011. The study investigated the potential of the mobile phone as a pedagogic tool in a senior secondary technical school. While the methods employed for data collection and analysis were conventional and uncontentious, a certain boldness and imaginative engagement with the empirical findings was deemed necessary in order generate a thesis that was both sufficiently substantial and original. However, an underlying tension operated wherein fundamentally philosophical impulses of the researcher had to be balanced against simultaneously present institutional expectations and practical imperatives. In particular, some key remarks of Heidegger concerning technology and thinking, vied for attention and prominence within the research project agenda. An articulation and elaboration of this underlying tension between the philosophical and the practical only became possible after the work was completed. The return and manifestation of these marginalised and latent issues are here given closer attention.